2020
DOI: 10.1007/s10803-020-04575-4
|View full text |Cite
|
Sign up to set email alerts
|

“I’m Proud to be a Little Bit Different”: The Effects of Autistic Individuals’ Perceptions of Autism and Autism Social Identity on Their Collective Self-esteem

Abstract: This study aimed to identify the attributes that autistic people perceive as positively and negatively impacting on their identity and wellbeing. In Study 1, we recruited 140 autistic participants for an online survey. Participants completed autism social identification and collective self-esteem measures and listed attributes they associated with autism. In Study 2, we conducted focus groups with 15 autistic people to explore how positively they perceived the attributes of autism. Participants then discussed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 32 publications
6
41
0
Order By: Relevance
“…This may be due to the fact that adolescence is the stage at which individuals are just starting to explore their identity and may face more pressure to fit into their peer groups (Drummond, 2013), while the transition to adulthood is a time when autistic individuals may be more likely to develop selfacceptance and self-advocacy skills (Lee et al, 2021). Studies outside of this review have also found that stronger affiliation with autistic identity is linked to higher collective selfesteem and improved mental health among autistic adults (K. Cooper et al, 2017;R. Cooper et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This may be due to the fact that adolescence is the stage at which individuals are just starting to explore their identity and may face more pressure to fit into their peer groups (Drummond, 2013), while the transition to adulthood is a time when autistic individuals may be more likely to develop selfacceptance and self-advocacy skills (Lee et al, 2021). Studies outside of this review have also found that stronger affiliation with autistic identity is linked to higher collective selfesteem and improved mental health among autistic adults (K. Cooper et al, 2017;R. Cooper et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…This may be due to the fact that adolescence is the stage at which individuals are just starting to explore their identity and may face more pressure to fit into their peer groups (Drummond, 2013), while the transition to adulthood is a time when autistic individuals may be more likely to develop self-acceptance and self-advocacy skills (Lee et al, 2021). Studies outside of this review have also found that stronger affiliation with autistic identity is linked to higher collective self-esteem and improved mental health among autistic adults (Cooper et al, 2017;Cooper et al, 2021). Meanwhile, stronger alignment with non-autistic culture has been linked to more positive selfperceptions among autistic adolescents (Cresswell & Cage, 2019), although this study's findings need to be interpreted with caution given the lack of overall significant effects and small sample size.…”
Section: Discussionmentioning
confidence: 96%
“…Examining the extent to which participants felt they identified as autistic might be something for future research to consider: we did not include this in our quantitative study, but the extent to which individuals feel strongly connected to an autistic identity could vary, and the strength of this identity could have relationships to well-being. 23 Asking participants to quantify the strength of their identification and validation could also allow for studies to examine how these factors change over time: this study used a cross-sectional design but longitudinal work that follows women through their diagnostic journeys would also allow for future examination of how diagnosis impact identity and well-being over time.…”
Section: Discussionmentioning
confidence: 99%
“…Collective self-esteem is the degree to which individuals perceive that they generally positively evaluate their social group (Cooper et al, 2021), better reflecting the psychological state of the users as community members. When the out-group threatens the realistic interests or cultural security of the in-group, it will influence its CS.…”
Section: The Mediating Role Of Csmentioning
confidence: 99%